Factors Influencing Financial Quality between Conventional and Islamic Banks in Indonesia - Zul Ihsan Mu'arrif (Program Studi Ekonomi Syariah, Fakultas Agama Islam Universitas Islam Riau, 2024)
This study examines the factors influencing financial quality between conventional and Islamic banks in Indonesia. Islamic banks operate without interest, focusing on economic justice, while conventional banks rely on interest rates. This research aims to identify and analyze the key factors affecting the financial quality of both types of banks. Panel data from annual financial reports (2008-2016) were analyzed using multivariate regression. The main findings indicate that Islamic banks are influenced by operational efficiency and net operating margin, whereas conventional banks are more affected by credit risk and operational management. These findings suggest that Islamic banks must enhance operational efficiency for profitability, while conventional banks should focus on risk management and cost efficiency. In conclusion, there are significant differences in the factors affecting the financial quality between the two types of banks, which is essential for policymakers and bank management.